Problematika Penegakan Hukum Tindak Pidana Pemilu Tahun 2024 oleh BAWASLU Kota Bengkulu - Al-Hafiz, Muhammad Iqbal; Syarkati (SiRad: Pelita Wawasan, 2025)
This research is motivated by the persistent occurrence of election violations, particularly electoral criminal offenses, many of which cannot be fully followed up by the Bengkulu City Election Supervisory Agency (Bawaslu). The aim of this study is to identify the forms of violations, the process of law enforcement, obstacles encountered, and the challenges faced by Bawaslu in carrying out its duties. This research employs a qualitative method with an empirical juridical approach. Data were collected through interviews with three informants from Bawaslu Bengkulu City and one reporting citizen, as well as through documentation and observation. The findings indicate that out of 41 alleged violations, 39 were officially registered, but only one was classified as a criminal offense and had to be discontinued at the Gakkumdu stage. The identified obstacles include weak evidence, low public participation, and a lack of synchronization among institutions within the Gakkumdu Center. In conclusion, law enforcement for electoral criminal offenses has not been running optimally due to unresolved issues in coordination, technical procedures, and public participation. [Penelitian ini dilatarbelakangi oleh masih banyaknya pelanggaran pemilu, khususnya tindak pidana pemilu, yang tidak seluruhnya dapat ditindaklanjuti oleh Bawaslu Kota Bengkulu. Tujuan penelitian ini untuk mengetahui bentuk pelanggaran, proses penegakan hukum, hambatan, serta problematika yang dihadapi oleh Bawaslu dalam menjalankan tugasnya. Penelitian ini menggunakan metode kualitatif dengan pendekatan yuridis empiris. Data diperoleh melalui wawancara dengan tiga informan dari Bawaslu Kota Bengkulu dan satu masyarakat pelapor, serta dokumentasi dan observasi. Hasil penelitian menunjukkan bahwa dari 41 dugaan pelanggaran dengan 39 pelanggaran yang terigestrasi, hanya satu yang dikategorikan sebagai tindak pidana dan harus terhenti di tahap Gakkumdu. Hambatan yang ditemukan antara lain lemahnya alat bukti, rendahnya partisipasi masyarakat, serta kurangnya sinkronisasi antar lembaga dalam Sentra Gakkumdu. Kesimpulannya, penegakan hukum terhadap tindak pidana pemilu belum berjalan optimal akibat problem koordinasi, teknis, dan partisipatif yang belum teratasi secara menyeluruh]